C3 Vertebral Metastases From Tongue Adenoid Cystic Carcinoma. Issue 27 (July 2015) - Feng, Helin; Wang, Jin; Guo, Peng; Xu, Jianfa; Feng, Jiangang; Wei., Leizhen
<x xml:space="preserve">Abstract</x> Abstract We report a rare case involving a patient with C3 vertebral body metastasis secondary to adenoid cystic carcinoma of the tongue. Five years after local resection of the primary tumor, magnetic resonance imaging showed a metastasis located in the left posterior border of the C3 vertebral body. Additionally, multiple pulmonary metastases were identified by computed tomography. Based on these findings, the patient underwent C2–3, C3–4 discectomy; C3 corpectomy; and titanium mesh fusion with a Zephir plate. The diagnosis was confirmed by the pathology findings. During 6 months of follow-up, the patient showed improvement and return of function of the cervical vertebrae, with no serious complications. Because of the scarcity of cases of vertebral metastases from tumors of the tongue in the literature, we have reported this case to add to the available evidence regarding this rarely encountered condition.